Exploring Bem's Self Perception Theory in Educational Context - Laila Mohebi; Fatima Bailey (University of Bologna, 2020)
Daryl Bem´s self-perception theory is a useful framework to create a better understanding of how the pre-service teachers develop and express their views and perceptions in an educational context. This study offers a synthesis of the main elements of Bem´s self-perception theory and compares it with the cognitive dissonance theory as valuable frameworks for educational policy and management. The self-perception concept is based on the assumption that people are what they do. In this sense, the relationship between self-perception and behaviour is of paramount importance. This study develops an overview of important self-perception psychological experiments and some applications of the theory to the field of educational policy design and management.